The Effect of Correctional Training Using Proposed Apparatus and Its Effect on Some Kinematical Variables for 200m Running for Runners U20 - Firas, Abdulla; Hussein, Ihab (Journal of Physical Education, 2022)
The research aimed at using training aids along with special trainings for specific distances for 200m running and power amount due to training with these aids for correcting performance. In addition to that, all mechanical conditions were corrected to achieve best angles, take off variables and acceleration. Thus, performance was corrected after performance analyses using Kenova to specify the weaknesses followed by the training program using proposed apparatus to develop the runner’s technique. The subjects were (6) youth 200m runners from Baghdad. The training program was applied for eight weeks with three training sessions per week. The results showed that using the proposed apparatus in 200m running training developed subject’s performance thus improved performance time as well as angles of some special movements.